3(4x+5)-2(3x-2)=3x+7

Simple and best practice solution for 3(4x+5)-2(3x-2)=3x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+5)-2(3x-2)=3x+7 equation:


Simplifying
3(4x + 5) + -2(3x + -2) = 3x + 7

Reorder the terms:
3(5 + 4x) + -2(3x + -2) = 3x + 7
(5 * 3 + 4x * 3) + -2(3x + -2) = 3x + 7
(15 + 12x) + -2(3x + -2) = 3x + 7

Reorder the terms:
15 + 12x + -2(-2 + 3x) = 3x + 7
15 + 12x + (-2 * -2 + 3x * -2) = 3x + 7
15 + 12x + (4 + -6x) = 3x + 7

Reorder the terms:
15 + 4 + 12x + -6x = 3x + 7

Combine like terms: 15 + 4 = 19
19 + 12x + -6x = 3x + 7

Combine like terms: 12x + -6x = 6x
19 + 6x = 3x + 7

Reorder the terms:
19 + 6x = 7 + 3x

Solving
19 + 6x = 7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
19 + 6x + -3x = 7 + 3x + -3x

Combine like terms: 6x + -3x = 3x
19 + 3x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
19 + 3x = 7 + 0
19 + 3x = 7

Add '-19' to each side of the equation.
19 + -19 + 3x = 7 + -19

Combine like terms: 19 + -19 = 0
0 + 3x = 7 + -19
3x = 7 + -19

Combine like terms: 7 + -19 = -12
3x = -12

Divide each side by '3'.
x = -4

Simplifying
x = -4

See similar equations:

| t*5-4=16 | | 20+3x-2=x^2-4x | | -4b=3(-4b)+7 | | 180=(8x)+x+90 | | 0.86(3.7-2.3x)=4.9 | | (7n-2)(5n-1)=0 | | 0.86(3.7-2.3x)=49 | | 30a^2+7a=0 | | (5v+7)(2+v)=0 | | g(-4b)=3(-4b)+7 | | 2x^3-8x^2-192x=0 | | 6cos+5tan=0 | | 5r+4r-9r= | | 6cisb+5tan=0 | | 2x=-10-2 | | 180=2x+76 | | 180=2x+76+(5x-2) | | 6(3x+5)-5(x-7)=39 | | c=6+5x | | 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= | | 2(8+6x)+2=4(4+3x)+2x | | 4a^3+12a^2-9a-27=0 | | 45+40a= | | 291.52=8(0.04m+27.70+0.20(27.70)) | | 8h+9=60 | | 21=(8-c)3 |

Equations solver categories